Сюжетно-ролевая игра в контексте развивающей предметно-пространственной среды ДОО в соответствии с ФГОС ДО - Ahtyrskaya Y. V., Korshunenko I. M., Semenova N. I. (Воспитание и обучение: теория, методика и практика, 2016)
the article deals with the organization of play activities of preschool children as a main activity in accordance with GEF TO. The developmental organization of subject-spatial environment in DRO that meets the requirements of the standard as part of maintaining emotional and psychological health of children.
Keywords: игровая деятельность; дошкольный возраст; сюжетно-ролевая игра; развивающая предметно-пространственная среда; центры активности; preschool age; play activity; educational subject-spatial environment; activity centres; maintaining emotional and psychological health; role-playing game; сохранение эмоционального здоровья; сохранение психологического здоровья